ARSITEKTUR TRADISONAL BALI PADA BANGUNAN PURI UBUD SEBAGAI POTENSI DAYA TARIK WISATA PRE-WEDDING - Ni Putu Krusita Candra Devi; I Dewa Gede Agung Diasana Putra (Sustainable, Planning and Culture (SPACE) : Jurnal Perencanaan Wilayah dan Kota, 2022)
Cultural tourism in the Ubud cannot be separated from the existence of Puri Ubud as landmark which is thick with cultural heritage and traditional Balinese architecture. In its development, special interest tours began to appear, such as pre-wedding tours with the concept of Bali Tempo Dulu. This study aims to identify the application of traditional Balinese architecture in Ubud Palace and its potential as a pre-wedding tourist attraction. The study used descriptive qualitative methods and data collection with secondary data from literature studies related to research. The results showed that the Sanga Mandala concept was applied to the arrangement of the Ubud Palace area, equipped with elements of traditional Balinese architecture such as the tembok penyengker, kori, candi bentar, natah, and buildings using the Tri Angga concept. With the existence of traditional Balinese architecture that is still preserved in Ubud Palace, it opens up the potential for the development of pre-wedding tourism as a tourist attraction. Pre-wedding tourism is expected to be able to preserve the traditional Balinese architecture, considering that the building or location with a traditional Balinese background is one of the main supporting factors in the pre-wedding concept with the theme of Bali Tempo Dulu.